(untitled) (Raparin Journal of Humanities (RJH), 2024)
Constantinople is the city that the Noble Messenger may God’s prayers and peace is upon him, announced his conquest by saying: “To conquer Constantinople, let us be the emir, its ruler, and the best army, that army. And the poets pay attention to it and write about it, as if this city was created to be a great empire that lasted for more than a thousand years. What helped it to survive is its huge building built by Emperor Constantine the Great in 324 AD to be the capital of the Eastern Byzantine Empire. This huge building is represented in its high fortified walls and its huge and remnant churches Now like the Hagia Sophia Church, and making it one of the most important cultural centers and a symbol of ancient civilization in addition to choosing this important geographical location, which gave it a very important economic and commercial importance, helped it to survive and continue and most of the attempts directed against it. Constantine’s great goal was to build it, to continue the survival of the European Empire (New Rome), but this time in the East with a new look and a new religion, which is Christianity by adopting the official religion of the new empire.